Diseño e implementación de un módulo electrónico para la automatización de un invernadero comunitario de producción de hortalizas y legumbres - Chafla Ruiz, Jaime Ernesto (2016)
The use of greenhouses is a need to produce crops that are out of season, thanks to this system you can control pests and reduce the use of fertilizers as well as improving production in harvest time. To this project was possible to design an electronic module for automation of irrigation and controlling the ambient temperature inside the greenhouse. To help of Concurrent Engineering and application QFD user needs that were transformed into technical specifications for the prototype, satisfying their requirements. Converting a greenhouse in an autonomous system, the use of various resources including the water was optimized, which is the most important in crop production was optimized, this was achieved by using sensors that monitor soil moisture and actuators allow the passage of water. Likewise, a better control of the temperature inside the greenhouse with the use of a sensor for monitoring environmental standards and a fan who handled the cooling had. The electronic module has an HMI screen in which the values of humidity and temperature are optimum for cultivation. And you can also choose 4 different crops: two vegetables (kidney tomato, carrot) and two legumes (beans and peas), which were selected because they are the most productive in the area.